Protective Effect of Topical Ibuprofen Against Dry Socket - Maha T Al–Saffar (Al-Rafidain Dental Journal, 2008)
Aims: To assess the clinical effect of topical preventive measures on the incdence of alveolar osteitis (dry socket) by inserting (either gelfoam sooked with ibuprofen suspension, or gelfoam sooked with metronidazole suspension, or gelfoam alone) in the extraction socket following removal of lower posterior teeth. Materials and Methods: One hundred eighty patients were included in the present study, (86) males and (94) females aged between 13–65 years, they were divided randomly into four treatment groups. The first group included 43 patients (control –ve),who received no topical medication following extraction.Whereas, in the second (control +ve) group which comprised 44 patients, gelfoam alone was inserted in the socket of extraction. While in the third group, gelfoam impregnated with metronidazole suspension was placed in the extraction socket, this group included 50 patients.However 43 patients treated in the fourth group, where gelfoam sooked with ibuprofen suspension was packed into the socket following extraction. Results: Comparison of the incidence of dry socket among the study groups were performed. Statistical analysis revealed that the prevalence of dry socket were significantly affected by the sex and tooth number. The topical application of ibuprofen provided a higher incidence of reduction in dry socket followed by metronidazole, while the application of gelfoam alone increased the incidence of this complication when compared with the remaining groups. Conclusion: This study showed that the topical ibuprofen suspension can be used as a prophylactic method to reduce the incidence of dry socket following removal of lower posterior teeth.